السمات الشخصية والأكاديمية لعضو هيئة التدريس الجامعي من وجهة نظر الأساتذة الجامعيين - عيادي, نادية; كشيشب, مراد (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى معرفة السمات الشخصية والأكاديمية لعضو هيئة التدريس الجامعي كما يراها الأساتذة الجامعيين، وتحديد ترتيبها، تم الاعتماد على المنهج الوصفي في الدراسة الميدانية وذلك من خلال تطبيق استبيان سمات الأستاذ الجامعي من إعداد الباحثين على عينة من الأستاذة الجامعيين بجامعة الشاذلي بن جديد، والذين بلغ عددهم 33 أستاذ وأستاذة، تمت معالجة البيانات باستخدام أسبيس وقد خلصت الدراسة إلى النتائج التالية: - أكد جميع أفراد عينة الدراسة على وجوب تميز الأستاذ الجامعي بمجموعة من السمات أهمها: الانضباط في العمل، القدرة على توصيل المادة العلمية، الطلاقة اللغوية وقوة الشخصية، الثقة بالنفس .... - السمات الأكاديمية احتلت المرتبة الأولى من حيث زجزب تميز الأستاذ الجامعي بها، تليها الصفات الشخصية. Abstract : this study aimed at identifying the personal and academic features of the university faculty as seen by the university professors, and determining its order, the descriptive curriculum was relied upon in the field study through the application of the university professor's attribute questionnaire prepared by researchers on a sample of the 33 university professors at Chadli Bin Jadid University, the data were processed using SPSS and the study concluded the following findings: - All members of the study sample stressed that the university professor must be distinguished by a set of features, the most important of which are: discipline at work, the ability to communicate scientific material, linguistic fluency and personality strength, self-confidence and other features. - Academic features ranked first in terms of the need for a university professor to be distinguished, followed by personality traits
مقال
Keywords: السمات الشخصية ; السمات الأكاديمية ; عضو هيئة التدريس ; الأستاذ الجامعي; personality traits; academic features; faculty member; university professor